OCCUPATIONAL STRESS AND BURNOUT SYNDROME: PROBLEMS OF CAUSATION (ACCORDING TO V.V. BOYKO'S QUESTIONNAIRE) - Бабанов, Сергей Анатольевич; Лысова, Маргарита Валериановна; Дарюхина, Екатерина Александровна; Бабанов, Андрей Сергеевич; Острякова, Наталья Александровна (Medicine in Kuzbass, 2025)
The aim of the research is to study the features of professional burnout among doctors of therapeutic (TR) and surgical (HR) profile in a specialized hospital.Materials and methods. The study was performed on the basis of the Department of Occupational Diseases and Clinical Pharmacology named after Professor V.V. Kosarev of the Samara State Medical University and the Department of Occupational Pathology of the Regional Center of Occupational Pathology of the Samara City Hospital N 5.The research was carried out within the framework of the department's comprehensive topic «Problems of polymorbidity, diagnosis, prognosis and prevention of occupational and production-related diseases in workers with isolated combined effects of environmental factors and the labor process» (registration number 124053000016-4), registration date 05/30/2024).The study included: group 1 – gastroenterologists (n = 52 people); group 2 – cardiologists (n = 58 people); group 3 – occupational oncologists (n = 48 people); group 4 – general surgeons (n = 71 people); group 5 – cardiosurgical surgeons (n = 30 people); group 6 – oncological surgeons (n = 65 people); group 7 – control group: employees of engineering, technical and economic specialties not related to work in medical organizations (healthy) (n = 75 people).The assessment of the level of professional burnout among medical workers was carried out according to the method of diagnosing the level of professional burnout by V.V. Boyko. At the same time, each component of «burnout» was diagnosed according to 4 signs forming the corresponding scales (V.V. Boyko, 2008, 2015).The statistical analysis was performed using the RStudio programming language and environment (R v.4.4.1, RStudio 2024.09.1+394). The χ2 criterion was used to compare the percentages. When evaluating differences in nonparametric data groups, the Mann-Whitney criteria were used for two comparison groups, and Kruskal-Wallis criteria for more than 2 groups.Results. The professional activity of doctors of therapeutic and surgical specialties is associated with the effects of chronic occupational stress, leading to the development of professional burnout.Limitations of the study. The study has regional (Samara region) and occupational (in terms of the detailed working conditions in the comparison groups studied) limitations.Conclusion. Thus, the data obtained indicate the need to use specialized rehabilitation measures for physicians using relaxation techniques, art therapy, as well as professional adaptation programs when identifying risk factors for increasing the level of professional burnout among medical workers who provide medical care in hospitals of TR, XP and specialized profiles.; physiotherapy techniques such as electroson and reflexotherapy, if possible, sanatorium-resort treatment in sanatoriums, local health resorts, etc. with visits to psychotherapy rooms, as well as psychopharmacological drugs
Keywords: professional burnout; medical workers; determinants of development